La Inquisició de València contra Vicent Navarro (1750-1757), Diego Ramírez (1742) i Pedro Navarro (1588), tres casos de bestialisme. - MOMPÓ NAVARRO, JACOB (Scripta, 2019)
Sodomy and bestiality have been considered throughout the Middle Ages and Modern Era as one of the greatest exponents of the sin of lust. The «ineffable crime», understood as a direct offense to God, was pursued by various judicial corpora throughout Christian Europe, and authors of the «crime against nature» were often condemned to the bonfire. However, regarding the processes we present here, the penalties the accused paid for their crimes became more benevolent than the death penalty. This is the case of Vicent Navarro, who exchanged capital punishment for galley penalty; or Pedro Navarro, who had to suffer from exile. We do not know the sentence of Diego Ramirez who, besides bestiality, was also accused of hermaphroditism and sodomy.